Impact of Communication Competency Training on Nursing Students' Self-advocacy Skills. Issue 5 (September 2016) - Doherty, Christi; Landry, Heidi; Pate, Barbara; Reid, Helen
Abstract : Deficiencies in nursing students' communication skills need to be addressed for students to influence and skillfully collaborate in crucial patient and self-advocacy conversations. This study evaluated the effectiveness of a communication competency educational program for nursing students (N = 61). A paired-sample t test determined that there was a statistical significance from pre to post intervention, indicating the importance of communication competency education for nursing students' ability to advocate for themselves and their patients.